Pengaruh Pengembangan Sumber Daya Manusia Terhadap Kinerja Pegawai pada Dinas Perhubungan Kota Samarinda (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of human resource development (HRD) on employee performance at the Department of Transportation in Samarinda City. HRD is a strategic factor in shaping adaptive and competent civil servants in response to the dynamic demands of public service bureaucracy. This quantitative research employed a survey method involving 84 employees, and the data were analyzed using simple linear regression with the aid of SPSS version 29. The findings indicate that HRD variables—comprising education, training, and career development—have a positive and significant effect on employee performance. The coefficient of determination (R²) of 0.362 indicates that 36.2% of the variation in employee performance is explained by HRD. These results emphasize the importance of systematic competency development programs to enhance productivity and service quality in local government transportation agencies.